Deep crustal composition and Late Paleozoic geotectonic evolution in West Junggar, China - Xu, Shenglin; Ding, Weicui; Ma, Feizhou; Chen, Xuanhua; Shao, Zhaogang; Han, Lele; Huang, Penghui; Shi, Jianjie; Yang, Xinru (Frontiers in Earth Science, 2025)
The West Junggar area in the southwestern part of the Central Asian Orogenic Belt (CAOB), is one of the largest areas of growth of the Phanerozoic crust in the world that has experienced intense Late Paleozoic magmatic activity, where crust-mantle interaction is significant. The issue of crustal growth has long been regarded as one of the most fundamental in earth sciences. In light of the challenges posed by the composition of deep materials and the Late Paleozoic crustal growth in the West Junggar area, there is a continued need to systematically determine the spatial distribution characteristics of deep materials in the crust, analysis the growth pattern and growth volume of the crust, and enhance the Late Paleozoic tectonic evolution of the region. Focusing on granite type Sr-Nd-Pb-Hf isotopic mapping, this study found that the West Junggar area has the isotopic characteristics of high positive εHf (t) and εNd (t), low (87 Sr/86 Sr)i, and young crustal mode age, there is almost no old crystalline basement in the deep crust. During the Late Paleozoic, about 85% of West Junggar had 75%–95% crustal growth, dominated by lateral crustal growth and material recirculation; about 15% of the area (connected to the Jietebudiao area) had 50%–75% crustal growth, dominated by vertical crustal growth. The West Junggar area mainly experienced four orogenic stages in the Late Paleozoic. In the Early Carboniferous period (360–320 Ma), there was significant intra-oceanic subduction, involving a substantial amount of juvenile material in lateral crustal accretion. The Late Carboniferous-Early Permian period (320–294 Ma) is the post-orogenic extension stage, during which a massive amount of juvenile mantle source was added. This resulted in the most intense magmatism and crustal growth, which could have the growth of the crust potentially more than 75%. In the Early Permian period (294–272 Ma), there was an intracontinental evolution stage and a decrease in the participation of juvenile material. During the Early Permian-Early Triassic period (272–250 Ma), magmatic activity decreased significantly, where the southwestern region experienced high-temperature, low-pressure, crustal thinning extension. Despite this, the crust received juvenile material, and plutonic magma intrusion occurred.